Asuhan Keperawatan Pada Tn. R Dengan Gangguan Sistem Pencernaan: Post Op Hemoroidektomi Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Khoerunnisa Dian Maulida; Ahmad Zakiudin; Yusriani Saleh Baso (STIKes Ibnu Sina Ajibarang, 2023)
Hemorrhoids are a common disease in society and have been around for a long time. In fact, many people do not/do not understand about health in the anorectal area. This causes prevalence data related to hemorrhoids to be limited and difficult to obtain because people (patients) are reluctant to go for medical examinations (Verawaty, 2022).